Semantic Adaptation using CCSL Clock Constraints - Boulanger, Frédéric; Dogui, Ayman; Hardebolle, Cécile; Jacquet, Christophe; Marcadet, Dominique; Prodan, Iuliana (Electronic Communications of the EASST, 2012)
When different parts of a system depend on different technical domains, the best suitable paradigm for modeling each part may differ. In this paper, we focus on the semantic adaptation between parts of a model which use different modeling paradigms in the context of model composition. We show how CCSL, a language for defining constraints and relations on clocks, can be used to define this semantic adaptation in a formal and modular way.